The Influence of Net Profit and Operating Cash Flow on Dividend in Transportation and Logistics Sector Companies Listed on the Indonesia Stock Exchange for the Period 2021-2023 - Iyus Sopian; Yusni Nuryani (Transpublika Publisher, 2025)
The industrial sector in Indonesia continues to expand rapidly, with transportation and logistics contributing 13.96% to national economic growth by the end of 2023. However, the COVID-19 pandemic created significant fluctuations in company profits and cash flows, influencing their ability to distribute dividends. Net income and operating cash flow thus become crucial indicators in financial statements, reflecting not only company performance but also investor considerations in dividend decisions. The objective of this research is to investigate the impact of net income and operating cash flow on dividend payouts within transportation and logistics firms that are publicly traded on the Indonesia Stock Exchange (IDX) from 2021 to 2023. This study utilized a quantitative methodology and focused on a total of 37 companies within this industry. Through purposive sampling methods, a sample of 7 companies was chosen for the study. The study relied on secondary data, gathered through literature review and documentation. Data analysis techniques included descriptive statistics, classical assumption tests, multiple linear regression, coefficient of determination, t-test, and F-test, utilizing SPSS Statistics version 26. The findings reveal three key results. First, net income has a significant partial effect on dividend distribution. Second, operating cash flow, when tested partially, shows no significant influence on dividends. Third, when considered simultaneously, both net income and operating cash flow significantly affect dividend payments. In conclusion, this study emphasizes that dividend policy in transportation and logistics companies is primarily determined by net income on an individual basis.